Examining the Role of Religious Product Consumption:Marketing to the Indian Ethnic Population of UK - Soni, Kanika (2008)
As the ethnic population of Indians rise across the U.K., the need and demand of cultural products are increasingly essential to retain the cultural value of their ethnic identity. This dissertation seeks to examine the role of marketing religious products of the various types of Hindu festivals towards the ethnic Indian community of UK, and examine the way these types of products are consumed. Using the literature review as a basis, the intent of this study is to develop a logical business model to cater to the Indian community in cities across the U.K. which are not within a close range to the bigger Indian communities, such as London (Southhall) and Birmingham, in which the unique products and services that are prevalent for each of the different Hindu festivals and culture are readily available. The model which is proposed to be developed is to open a physical store location and warehouse in the city of Nottingham and also reach the rest of England through an online shopping portal, which consumers can ÃÂ¢ÃÂÃÂone stop shopÃÂ¢ÃÂÃÂ. The model is thought through using previous studies and research of retailing and marketing towards an ethnic community and authors have discussed ways to reach out to the community and what approaches have been successful, leading towards an idea of an innovative strategy to develop a business model to reaching out to the untapped market within the Indian community. This business model with therefore be an initial stepping stone towards being able to understand the product consumption for products purchased for the major Hindu festivals.